Biochar rebuilds the network complexity of rare and abundant microbial taxa in reclaimed soil of mining areas to cooperatively avert cadmium stress - Zhu, Yanfeng; Ge, Xiaoping; Wang, Liping; You, Yunnan; Cheng, Yanjun; Ma, Jing; Chen, Fu (Frontiers in Microbiology, 2022)
Understanding the interactions between the soil microbial communities and species is critical in the remediation of heavy metal-contaminated soil. Biochar has been widely applied as a stabilizer in the in situ remediation of cadmium (Cd)-contaminated soils in mining areas. However, the rebuilding of the microbial taxa of rare and abundant species by biochar and their cooperative resistance to Cd stress remains elusive. In this pursuit, the present study envisaged the effects of two types of biochars viz., poplar bark biochar (PB) and thiourea-modified poplar bark biochar (TP) on the rare and abundant bacterial and fungal taxa by using pot experiments. The results demonstrated that the PB and TP treatments significantly reduced the leached Cd content, by 35.13% and 68.05%, respectively, compared with the control group (CK), in the reclaimed soil of the mining area. The application of biochar significantly improved the physicochemical properties like pH and Soil Organic Matter (SOM) of the soil. It was observed that TP treatment was superior to the PB and CK groups in increasing the diversity of the soil abundant and rare species of microbial taxa. Compared with the CK group, the application of PB and TP enhanced and elevated the complexity of the microbial networks of rare and abundant taxa, increased the number and types of network core microorganisms, reshaped the network core microorganisms and hubs, and boosted the microbial resistance to Cd stress. Our results indicate the response of rare and abundant microbial taxa to biochar application and the mechanism of their synergistic remediation of Cd-contaminated soil, thereby providing technical feasibility for in situ remediation of Cd-contaminated soil in mining areas.